A cost minimisation analysis in teledermatology: model-based approach - Eminović Nina; Dijkgraaf Marcel G; Berghout Rosanne M; Prins Astrid H; Bindels Patrick JE; de Keizer Nicolette F (BMC, 2010)
Abstract Background Although store-and-forward teledermatology is increasingly becoming popular, evidence on its effects on efficiency and costs is lacking. The aim of this study, performed in addition to a clustered randomised trial, was to investigate to what extent and under which conditions store-and-forward teledermatology can reduce costs from a societal perspective. Methods A cost minimisation study design (a model based approach) was applied to compare teledermatology and conventional process costs per dermatology patient care episode. Regarding the societal perspective, total mean costs of investment, general practitioner, dermatologists, out-of-pocket expenses and employer costs were calculated. Uncertainty analysis was performed using Monte Carlo simulation with 31 distributions in the used cost model. Scenario analysis was performed using one-way and two-way sensitivity analyses with the following variables: the patient travel distance to physician and dermatologist, the duration of teleconsultation activities, and the proportion of preventable consultations. Results Total mean costs of teledermatology process were €387 (95%CI, 281 to 502.5), while the total mean costs of conventional process costs were €354.0 (95%CI, 228.0 to 484.0). The total mean difference between the processes was €32.5 (95%CI, -29.0 to 74.7). Savings by teledermatology can be achieved if the distance to a dermatologist is larger (> = 75 km) or when more consultations (> = 37%) can be prevented due to teledermatology. Conclusions Teledermatology, when applied to all dermatology referrals, has a probability of 0.11 of being cost saving to society. In order to achieve cost savings by teledermatology, teledermatology should be applied in only those cases with a reasonable probability that a live consultation can be prevented. Trail Registration This study is performed partially based on PERFECT D Trial (Current Controlled Trials No.ISRCTN57478950).